Case Report: The first case of primary pulmonary collision tumor comprising mixed squamous cell and glandular papilloma and glomus tumor - Yang, Chan; Li, Shuang; Liang, Zuoyu; Jiang, Lili (Frontiers in Oncology, 2022)
Collision tumor is a rare entity, particularly occurring on the lungs. We report a case of a 57-year-old woman with a primary pulmonary collision tumor comprising mixed squamous cell and glandular papilloma and glomus tumor (GT). An abnormal mass was discovered in the right lung by computed tomography (CT) of the chest. A right lower lobectomy with mediastinal lymph node dissection was performed. Histological examination of the surgical specimen suggested that the lung cancer composed of two neoplastic components. To the best of our knowledge, this is the first report of a primary pulmonary collision tumor comprising two benign tumors of different origin, which were mixed squamous cell and glandular papilloma and glomus tumor.